Antagonistic activity endophytic bacteria isolate from oil palm roots against Ganoderma Sp. / Azerul Kamahudin - Kamahudin, Azerul (Faculty of Plantation and Agrotechnology, 2019)
The oil palm (Elaeis guineensis) is commodity crop for Malaysia. In this study, an experiment was conducted to screening antagonistic activity of endophytic bacteria from oil palm roots. The aims was to identify bacteria that can be used to control Ganoderma sp. Root sample was taken from three different place that is Segamat estate Johor, nursery Fong Shun trading Rompin and ladang uitm jasin, Melaka. For isolation of Ganoderma sp sample was being taken at private company research center at Gemencheh Melaka. A total of 30 roots sample were obtained with 10 sample from segamat estate Johor, 10 sample roots for in mature from nursery Fong Shun trading and 10 root samples form mature oil palm from ladang uitm Jasin. Bacteria that being isolates showed the antagonistic activity against Ganoderma sp by inhibition and slow down the growth rate of Ganoderma sp in culture plate. 27 endophytic bacteria were successfully isolated from roots sample and about 9 of it show the positive result, that slow down the growth of Ganoderma sp. Six out of 9 isolate were identified as Gram-negative bacteria and 3 were Gram-positive bacteria. Therefore, Gram-negative bacteria more in the oil palm roots compared to the Gram-positive bacteria. From 9 bacteria, only 2 bacteria that is success to suppress Ganoderma sp more the 50 % using the RIPG calculation method. These bacteria were identified and characterized. The bacteria colony form or shape is round and rod shape. Colony margin is entire and filamentous. Three type Colony elevation was identify that is raised, convex, and growth into medium.